ASSESSEMENT OF TROTOAR PHYSICAL CONDITIONS IN PURWOKERTO CITY, BANYUMAS DISTRICT - F eddy Poerwodihardjo; Corona Dwi Istiningsih (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Sidewalks are pedestrian paths that are generally parallel to the axis of the road and are higher thanthe surface of the pavement to ensure the safety of the pedestrians concerned. Will be assessed the suitabilityof the conditions of the sidewalk that was built in the city of Purwokerto with the Minister of Public WorksRegulation No. 03 of 2014 as a reference in the sidewalk development planning. Assessment includes;sidewalk dimensions, sidewalk surface conditions, drainage, and completeness of the sidewalk facilitiesThe author determines 9 observation sample locations to retrieve data on the sidewalk conditions thathave been built. The results of data collection in the form of a description of the pavement conditions in theform of qualitative data. Qualitative data is used as quantitative data so that it is easy to provide anassessment. Data is given a score, then the score for each location, so that the final results for each locationare obtained.The results of the overall assessment of the 9 sample locations are as follows; the sidewalk condition isvery good 11%, the sidewalk condition is 55% good, some 34% is not good so it is not suitable to be usedfor walking. Inadequate conditions need improvement to be used again.Keywords: sidewalk, regulations, assessmenABSTRAKTrotoar adalah jalur pejalan kaki yang umumnya sejajar dengan sumbu jalan dan lebih tinggi daripermukaan perkerasan jalan untuk menjamin keselamatan pejalan kaki yang bersangkutan. Akan dinilaikesesuaian kondisi trotoar yang terbangun di kota Purwokerto dengan Peraturan Menteri Pekerjaan UmumNomor 03 tahun 2014 sebagai acuan dalam perencanaan pembangunan trotoar. Penilaian meliputi; dimensitrotoar, kondisi permukaan trotoar, drainasi, dan kelengkapan fasilitas trotoar.Penulis menentukan 9 lokasi sampel pengamatan untuk diambil data kondisi trotoar yang telahterbangun. Hasil pengumpulkan data berupa deskripsi kondisi trotoar yang berupa data kualitatif. Datakualitatif dijadikan data kuantitatif agar mudah dalam memberi penilaian. Data diberi skor, selanjutnya skortiap lokasi , sehingga diperoleh hasil akhir tiap-tiap lokasi.Hasil dari penilaian secara keseluruhan dari 9 sampel lokasi adalah sebagai berikut: kondisi trotoarsangat baik 11 %, kondisi trotoar sebesar 55 % baik, sejumlah 34 % tidak baik sehingga tidak layakdigunakan untuk berjalan kaki. Kondisi yang tidak layak membutuhkan perbaikan agar dapat digunakankembali.Kata kunci : trotoar, peraturan, penilaian